2021
DOI: 10.1088/1361-6501/abe508
|View full text |Cite
|
Sign up to set email alerts
|

Reflective fiber-optic magnetic field sensor based on a magnetic-fluid-filled capillary probe structure

Abstract: A novel reflective magnetic field sensor is presented and experimentally demonstrated. The sensing probe is fabricated by splicing a section of uncoated four-core fiber (FCF) between two sections of no-core fibers (NCFs), and the end face of the last NCF is coated by silver. The sensor structure is sealed in a magnetic fluid (MF)-filled capillary, so that the NCF-FCF-NCF magnetic field sensing probe structure is obtained. The NCF is used to excite the high-order modes of the FCF's cladding. Combined with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The structure achieved stronger mode coupling with magnetic fluid and obtained a sensitivity of 0.336 dB/mT. Tao et al [ 17 ] proposed a fiber-optic magnetometer in which SMF-No core Fiber (NCF)-Few mode fiber (FMF)-NCF structure integrated with magnetic fluid is used. The magnetometer has a sensitivity of 0.30782 dB mT in the range of 0–18 mT.…”
Section: Introductionmentioning
confidence: 99%
“…The structure achieved stronger mode coupling with magnetic fluid and obtained a sensitivity of 0.336 dB/mT. Tao et al [ 17 ] proposed a fiber-optic magnetometer in which SMF-No core Fiber (NCF)-Few mode fiber (FMF)-NCF structure integrated with magnetic fluid is used. The magnetometer has a sensitivity of 0.30782 dB mT in the range of 0–18 mT.…”
Section: Introductionmentioning
confidence: 99%
“…By tapering FBG, the sensor can generate a powerful evanescent field in the sensing region. In 2021, Yu Tao et al [24] reported a reflective fiber magnetic field sensor. The fiber sensor is composed of an SMF-NCF-Few core fiber (FCF)-NCF structure and encapsulated by MF.…”
Section: Introductionmentioning
confidence: 99%